Prevalance of Depression and Its Association with Cigarette Smoking among Undergraduate Students; A Cross-Sectional Study from Karachi. - Abid, Zainab; Ramzan, Muhammad Adil; Sheroze, Muhammad Waqaruddin; Jamal, Kanwal; Batool, Rabisa; Mazher, Sumyyah (Jour Med Resh and Health Sci, 2022)
Introduction: University environment recognized as stressful and quiet often has a negative effect on student’s life. Several studies indicate that there is an increased rate of mental health disorders like depression among university students around the world. There are many studies conducted to find the prevalence of depression among medical students in different cities of Pakistan. However, very few studies have been conducted to find the frequency of depression among non-medical undergraduate students of Karachi. Therefore we conducted this study to find the frequency of depression and its association with smoking habit among undergraduate students. Materials and methods: This was a cross-sectional study conducted on the male students studying at the University of Karachi. A self-administered questionnaire having two parts was used to collect information from the participants. The first part was used to collect patients demographics and second part was used to assess depression. Data was analyzed using IBM SPSS V.20. Results: The frequency of depression among the study participants was found to be 80.5% (305). Among the study population 191(50.4%) were smokers and 188(49.6%) were non-smokers. Depression was observed in an overwhelming number of students who were smokers 168(87.9%). It was found that majority 229(60.4%) of the students did not had suicidal thoughts. Conclusion: Our study found a very high frequency of depression among university students. It also demonstrated an association between smoking and depression. We also found that the burden of smoking among students was significant.